Preparation method of positive electrode material for improving cycle performance of lithium battery

The hydrothermal method and calcination method are modified with the combined conductive agent, and the problem of insufficient stability and cycle life of lithium cobalt oxide at high voltage is solved, and the cycle stability and electrochemical performance of the battery are significantly improved.

CN119275282APending Publication Date: 2025-01-07JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411644858.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide cathode materials have insufficient stability and cycle life during high voltage charging and discharging, resulting in high cost and poor performance.

Method used

By mixing lithium cobalt oxide with dilute sulfuric acid, the crystal structure of S is stabilized, and V is introduced through calcining method, combining conductive agents such as conductive carbon black, modified graphene and carbon nanotubes to form a composite conductive to improve electrochemical properties.

Benefits of technology

The circulation stability of lithium cobalt oxide and the electrochemical performance of the battery are significantly improved, the probability of insufficient contact between the conductive agent and the active substance is reduced, the cost is reduced, and the circulation performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a positive electrode material for improving the cycle performance of a lithium battery, and relates to the technical field of battery preparation. Comprising the following steps: (1) mixing lithium cobalt oxide with dilute sulphuric acid, uniformly stirring, baking at 175-180 DEG C for 10-14 hours, filtering and drying to obtain primary modified lithium cobalt oxide; and (2) mixing the primary modified lithium cobalt oxide with vanadium pentoxide, mechanically grinding, introducing nitrogen, and calcining at 450-500 DEG C for 8-12 hours to obtain the positive electrode material. The preparation method has the beneficial effects that the positive electrode material is prepared by combining a hydrothermal method and a calcining method, so that the cycling stability of traditional lithium cobalt oxide is effectively improved; meanwhile, in a better scheme, a composite conductive agent is introduced, and materials in the composite conductive agent are modified, so that the electrochemical performance of the assembled battery is improved, and the cycle performance is more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery preparation, and in particular to a method for preparing a positive electrode material for improving the cycle performance of a lithium battery. Background Art

[0002] At present, new energy has been applied to all aspects of people's lives, and the development of lithium batteries in the fields of electronic products and power energy storage has also entered a mature stage. Lithium battery positive electrode materials are an important component of lithium-ion batteries and directly affect the performance of batteries, including energy density, cycle life and safety. At present, lithium cobalt oxide, ternary materials, lithium manganese oxide, lithium iron phosphate and other materials have occupied most of the positive electrode material share in the market.

[0003] As the main positive electrode material for consumer electronic batteries, lithium cobalt oxide has a layered structure that is more conducive to ion transmission and has higher voltage and energy density; however, with the increasing demand of consumers, its high cost and the instability of its crystal structure during high-voltage charging and discharging have been criticized. Therefore, how to improve the stability and cycle life of lithium cobalt oxide on a high-voltage charging and discharging platform has become a top priority. Therefore, the present invention obtains a method for preparing a positive electrode material that improves the cycle performance of a lithium battery. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a positive electrode material for improving the cycle performance of a lithium battery, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a positive electrode material for improving the cycle performance of a lithium battery comprises the following steps: (1) Mix lithium cobalt oxide and dilute sulfuric acid, stir evenly, bake at 175-180°C for 10-14 hours, filter, and dry to obtain primary modified lithium cobalt oxide; (2) The primary modified lithium cobalt oxide is mixed with vanadium pentoxide, mechanically ground, introduced with nitrogen, and calcined at 450-500°C for 8-12 hours to obtain a positive electrode material.

[0006] More optimally, the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1: (40-45); the mass ratio of lithium cobalt oxide to vanadium pentoxide is (45-50): 1; the process parameters of the calcination are: heating rate: 20-30°C / min, annealing rate: 8-12°C / min.

[0007] More optimally: the positive electrode sheet made of positive electrode material specifically includes the following steps: Step 1: Mix the positive electrode material with the binder and the conductive agent, and stir evenly to obtain a positive electrode slurry; Step 2: Evenly coat the positive electrode slurry on the aluminum foil, and vacuum dry it at 100-140°C for 8-14 hours to obtain a positive electrode sheet.

[0008] More optimally: in the positive electrode slurry, the mass ratio of the positive electrode material, the adhesive, and the conductive agent is 95.6:2.2:2.2; the adhesive includes but is not limited to polyvinylidene fluoride; and the conductive agent includes conductive carbon black.

[0009] More optimally: the conductive agent is obtained by compounding conductive carbon black, modified graphene and modified carbon nanotubes, wherein the mass ratio of conductive carbon black, modified graphene and modified carbon nanotubes is (2.5-3): (1.2-1.5): (2-3).

[0010] More optimally: the preparation process of the modified graphene is: S1: Under a protective atmosphere, lauric acid and hydroxyethylethylenediamine are mixed, and dehydrated at 110-120°C for 1-2 hours under reduced pressure, and then the temperature is continuously raised to 250-300°C, and the reaction is performed for 2-3 hours. The mixture is cooled, and chloroacetic acid is then added, and the temperature is raised to 100-120°C, and the reaction is performed for 3-4 hours to obtain intermediate A. S2: adding graphene oxide and γ-aminopropyltriethoxysilane to N,N-dimethylformamide, heating to 70-90° C., stirring and reacting for 5-7 hours to obtain amino graphene; S3: under a protective atmosphere, add the amino graphene and intermediate A to dichloromethane, stir evenly, then add 4-dimethylaminopyridine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, heat to 70-80° C., react for 3-4 hours, and obtain intermediate B; S4: Under a protective atmosphere, the intermediate B is mixed with dichloromethane, chloroacetic acid and sodium hydroxide are added, the temperature is raised to 100-110° C., and the reaction is carried out for 1-2 hours to obtain modified graphene.

[0011] Preferably, the intermediate A comprises the following components: by weight, 200-220 parts of lauric acid, 100-110 parts of hydroxyethylethylenediamine, and 90-95 parts of chloroacetic acid; The amino graphene comprises the following components: by weight, 20-25 parts of graphene oxide, 30-35 parts of γ-aminopropyltriethoxysilane, and 200-250 parts of N,N-dimethylformamide; The intermediate B comprises the following components: by weight, 10-12 parts of amination graphene, 20-22 parts of intermediate A, 200-250 parts of dichloromethane, 0.1-0.2 parts of 4-dimethylaminopyridine, and 0.1-0.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; The modified graphene comprises the following components: by weight, 20-25 parts of intermediate B, 200-250 parts of dichloromethane, 80-85 parts of chloroacetic acid, and 20-25 parts of sodium hydroxide.

[0012] More optimally: the preparation process of the modified carbon nanotubes is: 1): Evenly mix the acidified carbon nanotubes, γ-aminopropyltriethoxysilane and deionized water, react at 70-80°C for 1-2h, filter, wash and dry to obtain the amino carbon nanotubes after the reaction is complete; 2): Under a protective atmosphere, add the amino carbon nanotubes, triethylamine, and intermediate A to dichloromethane, stir evenly, heat to 50-60°C, react for 1-2 hours, cool to room temperature, then add chloroacetic acid and sodium hydroxide, heat to 90-100°C, react for 2-3 hours, and obtain a primary modified carbon nanotube; 3): Add the once modified carbon nanotubes into the magnesium sulfate solution, disperse them by ultrasonic for 1-2 hours, dry them, heat them to 800-850°C, maintain them for 1-2 hours, cool them to room temperature, wash them, and dry them to obtain modified carbon nanotubes.

[0013] More optimally: the preparation process of the modified carbon nanotubes is: the amination carbon nanotubes include the following components: by weight, 10-12 parts of acidified carbon nanotubes, 20-25 parts of γ-aminopropyltriethoxysilane, and 100-150 parts of deionized water; The primary modified carbon nanotubes comprise the following components: by weight, 10-12 parts of amino carbon nanotubes, 0.1-0.2 parts of triethylamine, 8-10 parts of intermediate A, 100-150 parts of dichloromethane, 5-6 parts of chloroacetic acid, 1-2 parts of sodium hydroxide; The modified carbon nanotubes include the following components: by weight, 10-12 parts of primary modified carbon nanotubes and 100-120 parts of magnesium sulfate solution.

[0014] Compared with the prior art, the beneficial effects of the present application are as follows: the present invention prepares the positive electrode material by combining the hydrothermal method and the calcination method, which effectively improves the cycle stability of the traditional lithium cobalt oxide; at the same time, in the preferred scheme, the composite conductive agent is introduced and the materials therein are modified, so that the electrochemical performance of the assembled battery is improved and the cycle performance is more stable, as follows: First: In the scheme, conventional lithium cobalt oxide material is dissolved in dilute sulfuric acid, and S element is doped by hydrothermal synthesis method, CoO6 polyhedron and tetrahedron (SO4) 2-The strong covalent bonds between the structures can stabilize the crystal structure and improve the cycle performance; the V element is then introduced by calcination, and the V doped into the oxygen vacancies in the conventional lithium cobalt oxide significantly reduces the irreversible O2 escape compared to the original lithium cobalt oxide. The introduced V also increases the phase transition energy barrier and Co 3+ Migration, thereby further improving the cycle stability of traditional lithium cobalt oxide; Second, conductive carbon black has poor conductivity and usually requires a higher addition amount to improve electrochemical performance. Therefore, this scheme further introduces one-dimensional carbon nanotubes and two-dimensional graphene oxide. Since carbon nanotubes have a larger aspect ratio and a larger specific surface area, they can be overlapped on the surface of active material particles to form electron transport channels. Graphene oxide can provide a supporting platform to build a complete conductive network. Therefore, the synergistic effect of the three can reduce the probability of insufficient contact between the conductive agent and the active material, thereby reducing costs and improving the cycle performance of the battery.

[0015] In the optimization scheme, due to the high specific surface energy of carbon nanotubes, agglomeration is very likely to occur. In addition to the conductive carbon black that can be interspersed between the carbon nanotubes and the graphene sheets to improve the dispersion effect of the two, the present invention also chemically modifies the surfaces of the carbon nanotubes and graphene. The introduced imidazole groups can improve the dispersion of the two through hydrogen bonding, π-π interaction and cation-π interaction to avoid agglomeration. At the same time, in order to further improve the conductive properties of the carbon nanotubes, the present invention introduces sulfur, which can effectively improve the capacity and rate performance of the carbon nanotubes, thereby improving the performance. DETAILED DESCRIPTION

[0016] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0017] It should be noted that the following parts are parts by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, lauric acid CAS is 143-07-7, and the manufacturer is Jiangsu Runfeng Synthetic Technology Co., Ltd.; hydroxyethylethylenediamine CAS is 111-41-1, and the manufacturer is Wuhan Kanos Technology Co., Ltd.; chloroacetic acid CAS is 79-11-8, and the manufacturer is Dalian Yide Rui Chemical Co., Ltd.; γ-aminopropyltriethoxysilane CAS is 919-30-2; 4-dimethylaminopyridine CAS is 1122-58-3; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride CAS is 25952-53-8. Example

[0018] The preparation process of positive electrode material includes the following steps: (1) mixing lithium cobalt oxide and dilute sulfuric acid, wherein the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:45, stirring evenly, baking at 180° C. for 12 hours, filtering, and drying to obtain primary modified lithium cobalt oxide; (2) mixing the primary modified lithium cobalt oxide with vanadium pentoxide, wherein the mass ratio of lithium cobalt oxide to vanadium pentoxide is 45:1, mechanically grinding, introducing nitrogen, and calcining at 500°C for 10 hours to obtain a positive electrode material; The preparation process of the positive electrode sheet includes the following steps: Step 1: Mix the positive electrode material with the binder (polyvinylidene fluoride) and the conductive agent (conductive carbon black), stir evenly, and obtain a positive electrode slurry; wherein the mass ratio of the positive electrode material, the binder, and the conductive agent is 95.6:2.2:2.2 Step 2: Evenly coat the positive electrode slurry on the aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a positive electrode sheet.

[0019] Example 2: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:35.

[0020] Example 3: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:40.

[0021] Example 4: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:50.

[0022] Example 5: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:55.

[0023] Example 6: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to vanadium pentoxide is 40:1.

[0024] Example 7: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to vanadium pentoxide is 50:1.

[0025] Example 8: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to vanadium pentoxide is 55:1.

[0026] Example 9: is basically the same as Example 1, except that the mass ratio of lithium cobalt oxide to vanadium pentoxide is 60:1.

[0027] Comparative Example 1: is basically the same as Example 1, except that the S element is not introduced through the hydrothermal synthesis reaction.

[0028] Comparative Example 2: basically the same as Example 1, except that the V element is not introduced by calcination.

[0029] Comparative Example 3: Basically the same as Example 1, except that the positive electrode material uses traditional lithium cobalt oxide.

[0030] Comparative Example 4: The conductive agent is a mixture of conductive carbon black, modified graphene, and modified carbon nanotubes, as follows: The preparation process of positive electrode material includes the following steps: (1) mixing lithium cobalt oxide and dilute sulfuric acid, wherein the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:45, stirring evenly, baking at 180° C. for 12 hours, filtering, and drying to obtain primary modified lithium cobalt oxide; (2) mixing the primary modified lithium cobalt oxide with vanadium pentoxide, wherein the mass ratio of lithium cobalt oxide to vanadium pentoxide is 45:1, mechanically grinding, introducing nitrogen, and calcining at 500°C for 10 hours to obtain a positive electrode material; The preparation process of the positive electrode sheet includes the following steps: Step 1: Mix the positive electrode material with a binder (polyvinylidene fluoride) and a conductive agent (the mass ratio of conductive carbon black, modified graphene, and modified carbon nanotubes is 3:1.2:2), stir evenly, and obtain a positive electrode slurry; wherein the mass ratio of the positive electrode material, the binder, and the conductive agent is 95.6:2.2:2.2; Step 2: Evenly coat the positive electrode slurry on the aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a positive electrode sheet.

[0031] Wherein, the preparation process of modified graphene is: S1: Under nitrogen, 220 parts of lauric acid and 110 parts of hydroxyethylethylenediamine were mixed, and dehydrated at 120°C for 2 hours under reduced pressure, and then the temperature was further raised to 300°C, and the reaction was continued for 3 hours. After cooling, 95 parts of chloroacetic acid were added, and the temperature was raised to 120°C, and the reaction was continued for 4 hours to obtain intermediate A; S2: Add 25 parts of graphene oxide and 35 parts of γ-aminopropyltriethoxysilane to 250 parts of N,N-dimethylformamide, raise the temperature to 90°C, and stir the reaction for 7 hours to obtain amino graphene; S3: Under nitrogen, 12 parts of amino graphene and 22 parts of intermediate A were added to 250 parts of dichloromethane, stirred evenly, and then 0.2 parts of 4-dimethylaminopyridine and 0.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added, the temperature was raised to 80°C, and the reaction was carried out for 4 hours to obtain intermediate B; S4: Under nitrogen, 25 parts of intermediate B were mixed with 250 parts of dichloromethane, 85 parts of chloroacetic acid and 25 parts of sodium hydroxide were added, the temperature was raised to 110° C., and the reaction was carried out for 2 hours to obtain modified graphene; The preparation process of modified carbon nanotubes is: 1): 12 parts of acidified carbon nanotubes, 25 parts of γ-aminopropyltriethoxysilane and 50 parts of deionized water were mixed evenly, reacted at 80° C. for 2 hours, and after the reaction was complete, filtered, washed and dried to obtain amino carbon nanotubes; 2): Under nitrogen, 12 parts of amino carbon nanotubes, 0.2 parts of triethylamine, and 10 parts of intermediate A were added to 150 parts of dichloromethane, stirred evenly, heated to 60°C, reacted for 2 hours, cooled to room temperature, and then 6 parts of chloroacetic acid and 2 parts of sodium hydroxide were added, heated to 100°C, and reacted for 3 hours to obtain primary modified carbon nanotubes; 3): Add 12 parts of the once modified carbon nanotubes to 120 parts of magnesium sulfate solution, disperse them by ultrasonication for 2 hours, dry them, heat them to 850°C, maintain them for 2 hours, cool them to room temperature, wash them, and dry them to obtain modified carbon nanotubes.

[0032] Comparative Example 5: Based on Comparative Example 4, the carbon nanotubes are not doped with S element, as follows: The preparation process of positive electrode material includes the following steps: (1) mixing lithium cobalt oxide and dilute sulfuric acid, wherein the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:45, stirring evenly, baking at 180° C. for 12 hours, filtering, and drying to obtain primary modified lithium cobalt oxide; (2) mixing the primary modified lithium cobalt oxide with vanadium pentoxide, wherein the mass ratio of lithium cobalt oxide to vanadium pentoxide is 45:1, mechanically grinding, introducing nitrogen, and calcining at 500°C for 10 hours to obtain a positive electrode material; The preparation process of the positive electrode sheet includes the following steps: Step 1: Mix the positive electrode material with a binder (polyvinylidene fluoride) and a conductive agent (the mass ratio of conductive carbon black, modified graphene, and modified carbon nanotubes is 3:1.2:2), stir evenly, and obtain a positive electrode slurry; wherein the mass ratio of the positive electrode material, the binder, and the conductive agent is 95.6:2.2:2.2; Step 2: Evenly coat the positive electrode slurry on the aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a positive electrode sheet.

[0033] Wherein, the preparation process of modified graphene is: S1: Under nitrogen, 220 parts of lauric acid and 110 parts of hydroxyethylethylenediamine were mixed, and dehydrated at 120°C for 2 hours under reduced pressure, and then the temperature was further raised to 300°C, and the reaction was continued for 3 hours. After cooling, 95 parts of chloroacetic acid were added, and the temperature was raised to 120°C, and the reaction was continued for 4 hours to obtain intermediate A; S2: Add 25 parts of graphene oxide and 35 parts of γ-aminopropyltriethoxysilane to 250 parts of N,N-dimethylformamide, raise the temperature to 90°C, and stir the reaction for 7 hours to obtain amino graphene; S3: Under nitrogen, 12 parts of amino graphene and 22 parts of intermediate A were added to 250 parts of dichloromethane, stirred evenly, and then 0.2 parts of 4-dimethylaminopyridine and 0.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added, the temperature was raised to 80°C, and the reaction was carried out for 4 hours to obtain intermediate B; S4: Under nitrogen, 25 parts of intermediate B were mixed with 250 parts of dichloromethane, 85 parts of chloroacetic acid and 25 parts of sodium hydroxide were added, the temperature was raised to 110° C., and the reaction was carried out for 2 hours to obtain modified graphene; The preparation process of modified carbon nanotubes is: 1): 12 parts of acidified carbon nanotubes, 25 parts of γ-aminopropyltriethoxysilane and 50 parts of deionized water were mixed evenly, reacted at 80° C. for 2 hours, and after the reaction was complete, filtered, washed and dried to obtain amino carbon nanotubes; 2): Under nitrogen, add 12 parts of amino carbon nanotubes, 0.2 parts of triethylamine, and 10 parts of intermediate A to 150 parts of dichloromethane, stir evenly, heat to 60°C, react for 2 hours, cool to room temperature, then add 6 parts of chloroacetic acid and 2 parts of sodium hydroxide, heat to 100°C, react for 3 hours, and obtain modified carbon nanotubes.

[0034] Comparative Example 6: Based on Comparative Example 4, the carbon nanotubes and graphene are not modified, as follows: The preparation process of positive electrode material includes the following steps: (1) mixing lithium cobalt oxide and dilute sulfuric acid, wherein the mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1:45, stirring evenly, baking at 180° C. for 12 hours, filtering, and drying to obtain primary modified lithium cobalt oxide; (2) mixing the primary modified lithium cobalt oxide with vanadium pentoxide, wherein the mass ratio of lithium cobalt oxide to vanadium pentoxide is 45:1, mechanically grinding, introducing nitrogen, and calcining at 500°C for 10 hours to obtain a positive electrode material; The preparation process of the positive electrode sheet includes the following steps: Step 1: Mix the positive electrode material with a binder (polyvinylidene fluoride) and a conductive agent (the mass ratio of conductive carbon black, graphene oxide, and carbon nanotubes is 3:1.2:2), stir evenly, and obtain a positive electrode slurry; wherein the mass ratio of the positive electrode material, the binder, and the conductive agent is 95.6:2.2:2.2; Step 2: Evenly coat the positive electrode slurry on the aluminum foil, and vacuum dry it at 120° C. for 12 hours to obtain a positive electrode sheet.

[0035] Testing experiment: The positive electrode sheets prepared in Examples 1-9 and Comparative Examples 1-6 were assembled into lithium batteries in a glove box filled with argon gas according to the assembly sequence of "battery shell - placing positive electrode sheets - dripping electrolyte - placing diaphragm - dripping electrolyte - placing lithium sheets - placing gasket shrapnel - battery shell"; then the lithium batteries were subjected to 10, 30, and 50 cycles of 0.2C charge and discharge tests using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A), with a voltage range of 3.0-4.6V. The test results are shown in the following table: Table 1

[0036] Conclusion: Compared with Example 3, Example 1 prepares the positive electrode material by combining the hydrothermal method and the calcination method, which effectively improves the cycle stability of the traditional lithium cobalt oxide. At the same time, Comparative Example 4 introduces a composite conductive agent on the basis of Example 1, and modifies the materials therein, so that the electrochemical performance of the assembled battery is improved, and the cycle performance is more stable, which is in line with practical applications.

[0037] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for improving the cycle performance of a lithium battery, characterized in that: The preparation steps of the positive electrode material are: (1) Mix lithium cobalt oxide and dilute sulfuric acid, stir evenly, bake at 175-180°C for 10-14 hours, filter, and dry to obtain primary modified lithium cobalt oxide; (2) The primary modified lithium cobalt oxide is mixed with vanadium pentoxide, mechanically ground, introduced with nitrogen, and calcined at 450-500°C for 8-12 hours to obtain a positive electrode material.

2. A method for preparing a positive electrode material for improving the cycle performance of a lithium battery according to claim 1, characterized in that: The mass ratio of lithium cobalt oxide to dilute sulfuric acid is 1: (40-45); the mass ratio of lithium cobalt oxide to vanadium pentoxide is (45-50): 1; the process parameters of the calcination are: heating rate: 20-30°C / min, annealing rate: 8-12°C / min.

3. A positive electrode material, characterized in that: The positive electrode material is obtained by the preparation method described in claim 1.

4. A method for preparing a positive electrode sheet, characterized in that: The following steps are involved: Step 1: Mix the positive electrode material according to claim 3 with a binder and a conductive agent, and stir them evenly to obtain a positive electrode slurry; Step 2: Evenly coat the positive electrode slurry on the aluminum foil, and vacuum dry it at 100-140°C for 8-14 hours to obtain a positive electrode sheet.

5. The method for preparing a positive electrode sheet according to claim 4, characterized in that: In the positive electrode slurry, the mass ratio of the positive electrode material, the adhesive and the conductive agent is 95.6:2.2:2.2; the adhesive includes polyvinylidene fluoride; and the conductive agent includes conductive carbon black.

6. The method for preparing a positive electrode sheet according to claim 5, characterized in that: The conductive agent also includes modified graphene and modified carbon nanotubes, wherein the mass ratio of conductive carbon black, modified graphene and modified carbon nanotubes is (2.5-3): (1.2-1.5): (2-3).

7. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The preparation process of the modified graphene is: S1: Under a protective atmosphere, lauric acid and hydroxyethylethylenediamine are mixed, and dehydrated at 110-120°C for 1-2 hours under reduced pressure, and then the temperature is continuously raised to 250-300°C, and the reaction is performed for 2-3 hours. The mixture is cooled, and chloroacetic acid is then added, and the temperature is raised to 100-120°C, and the reaction is performed for 3-4 hours to obtain intermediate A. S2: adding graphene oxide and γ-aminopropyltriethoxysilane to N,N-dimethylformamide, heating to 70-90° C., stirring and reacting for 5-7 hours to obtain amino graphene; S3: under a protective atmosphere, add the amino graphene and intermediate A to dichloromethane, stir evenly, then add 4-dimethylaminopyridine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, heat to 70-80° C., react for 3-4 hours, and obtain intermediate B; S4: Under a protective atmosphere, the intermediate B is mixed with dichloromethane, chloroacetic acid and sodium hydroxide are added, the temperature is raised to 100-110° C., and the reaction is carried out for 1-2 hours to obtain modified graphene.

8. The method for preparing a positive electrode sheet according to claim 7, characterized in that: The intermediate A comprises the following components: by weight, 200-220 parts of lauric acid, 100-110 parts of hydroxyethylethylenediamine, and 90-95 parts of chloroacetic acid; The amino graphene comprises the following components: by weight, 20-25 parts of graphene oxide, 30-35 parts of γ-aminopropyltriethoxysilane, and 200-250 parts of N,N-dimethylformamide; The intermediate B comprises the following components: by weight, 10-12 parts of amination graphene, 20-22 parts of intermediate A, 200-250 parts of dichloromethane, 0.1-0.2 parts of 4-dimethylaminopyridine, and 0.1-0.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; The modified graphene comprises the following components: by weight, 20-25 parts of intermediate B, 200-250 parts of dichloromethane, 80-85 parts of chloroacetic acid, and 20-25 parts of sodium hydroxide.

9. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The preparation process of the modified carbon nanotubes is as follows: 1): Evenly mix the acidified carbon nanotubes, γ-aminopropyltriethoxysilane and deionized water, react at 70-80°C for 1-2h, filter, wash and dry to obtain the amino carbon nanotubes after the reaction is complete; 2): Under a protective atmosphere, add the amino carbon nanotubes, triethylamine, and intermediate A to dichloromethane, stir evenly, heat to 50-60°C, react for 1-2 hours, cool to room temperature, then add chloroacetic acid and sodium hydroxide, heat to 90-100°C, react for 2-3 hours, and obtain a primary modified carbon nanotube; 3): Add the once modified carbon nanotubes into the magnesium sulfate solution, disperse them by ultrasonic for 1-2 hours, dry them, heat them to 800-850°C, maintain them for 1-2 hours, cool them to room temperature, wash them, and dry them to obtain modified carbon nanotubes.

10. The method for preparing a positive electrode sheet according to claim 9, characterized in that: The preparation process of the modified carbon nanotubes is as follows: the amination carbon nanotubes include the following components: by weight, 10-12 parts of acidified carbon nanotubes, 20-25 parts of γ-aminopropyltriethoxysilane, and 100-150 parts of deionized water; The primary modified carbon nanotubes include the following components: by weight, 10-12 parts of amino carbon nanotubes, 0.1-0.2 parts of triethylamine, 8-10 parts of intermediate A, 100-150 parts of dichloromethane, 5-6 parts of chloroacetic acid, and 1-2 parts of sodium hydroxide; The modified carbon nanotubes include the following components: by weight, 10-12 parts of primary modified carbon nanotubes and 100-120 parts of magnesium sulfate solution.

Citation Information

Cited By

  • Positive electrode material for improving performance of LMFP battery and preparation method of positive electrode material

    CN119864406A